Partial substitution of prague powder with sorbic acid in quick cured ham - Villalba, Ma. Rica A.
Prague powder levels reduced to 75%, 50% and 25% (by weight) were partially substituted with 0.26% level sorbic acid (by weight) in quick cured ham. Residual nitrate levels, pH, color and % WHC of the samples, including a control (100% prague powder level), were determined after one week and two weeks of storage. Microbiological and sensory properties of the samples were likewise evaluated. residual nitrate decreased considerably with input prague powder levels and upon longer storage. The pH of the samples were favorable conditions against nitrosation and for antimicrobial action of sorbic acid. Better water holding capacity was achieved in the prague powder-substituted samples. The control and test samples of quick cured ham gave negative results for anaerobic and gas-forming bacteria, and total plate counts were observed to be far below microbial standards for frozen precooked meats. Color scores of the samples decreased with reduced prague powder levels, as confirmed by correlation tests between residual nitrite levels and color evaluation scores. Statistical analysis showed no significant difference among the 4 samples with respect to flavor, tenderness and juiciness after one and two weeks of storage. the highest scores on general acceptability were obtained by the sample with 50% prague powder level.